2018
DOI: 10.3758/s13428-018-1121-9
|View full text |Cite
|
Sign up to set email alerts
|

Questions on honest responding

Abstract: This article presents a new method for reducing socially desirable responding in Internet self-reports of desirable and undesirable behavior. The method is based on moving the request for honest responding, often included in the introduction to surveys, to the questioning phase of the survey. Over a quarter of Internet survey participants do not read survey instructions, and therefore, instead of asking respondents to answer honestly, they were asked whether they responded honestly. Posing the honesty message … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…(1) As the pretests showed that at least 3 min were needed to complete the survey, participants who spent less than 200 s were excluded from analyses; (2) To avoid careless and untrustworthy responses, one attention check question was imbedded in the middle of the questionnaire ("If you see this question, please select "Extremely"). If a participant failed this check, his/her data were excluded from analyses; (3) To reduce social desirability, which is prone in self-report measures, we imbedded two honest response questions suggested by Vésteinsdóttir et al (2019). All cases that failed this check were excluded from analyses.…”
Section: Methodsmentioning
confidence: 99%
“…(1) As the pretests showed that at least 3 min were needed to complete the survey, participants who spent less than 200 s were excluded from analyses; (2) To avoid careless and untrustworthy responses, one attention check question was imbedded in the middle of the questionnaire ("If you see this question, please select "Extremely"). If a participant failed this check, his/her data were excluded from analyses; (3) To reduce social desirability, which is prone in self-report measures, we imbedded two honest response questions suggested by Vésteinsdóttir et al (2019). All cases that failed this check were excluded from analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Individualism puts individuals in the center of attention and emphasizes personal interests, individual values/goals, and independence of individuals. Collectivism, in contrast, prioritizes the group over the self and underlines collective interests, common values/goals, and interdependence of individuals (Hofstede, 1980;Triandis, 1995). Individualism and collectivism are among the most frequently studied cultural dimensions in psychological and social sciences (see a review, Oyserman et al, 2002;Taras et al, 2010) and have been often applied to explain the differences between the East and the West in creativity studies as well (e.g., Niu and Sternberg, 2001;Yi et al, 2013;Tang et al, 2018).…”
Section: Individualism Vs Collectivism Well-being and Social Connementioning
confidence: 99%
“…The cognitive interviews are considered the means to reveal these processes and, thus, contribute to the meaningfulness of a questionnaire as judged by the responders. There is, however, a risk that this process ignores the fact that responders (unconsciously) tend to answer in a socially desirable manner (fake good) (25,26), and sometimes seek to give answers conforming to what they think is expected from them (27).…”
Section: Discussionmentioning
confidence: 99%